Diagnostics of Paternal-Child’s Relations as Means of Rendering of Educational Consultative Help to Incomplete Family - Myroslava Hryzhak (Pedagogical Discourse, 2012)
The problems of diagnostics of paternal-child’s relations as pre-conditions of rendering of educational consultative help to incomplete family are highlighted in the article. The methods of studying of paternal-child’s relations, microclimate of family, formed personal qualities of children from incomplete families, and also state of rendering of such help to modern incomplete family are characterized in the article.